Odpowiedzi

Najlepsza Odpowiedź!
2010-01-24T19:28:44+01:00
3(x+y) - 5(x-y) = 3x + 3y - 5x + 5y = -2x + 7y

(3a-b) 4ab = 12a²b - 4ab²

(5a+b) (4a+b) = 20a² + 5ab + 4ab + b² = 20a² + 9ab + b²

(2x+5) do kwadratu = (2x+5)(2x+5) = 4x² + 10x + 10x + 25 = 4x² + 20x + 25

(5 y+ 4) do kwadratu = (5 y+ 4)(5 y+ 4) = 25y² + 20y + 20y + 16 = 25y² + 40y + 16

( 1/2 x - 2 ) do kwadratu = ( 1/2 x - 2 )( 1/2 x - 2 ) = 0,25x² - x - x + 4 = 0,25x² - 2x + 4
2010-01-24T19:35:25+01:00
A)3(x+y) - 5(x-y)= 3x+3y-5x+5y=-2x+8y
b) (3a-b) 4ab= 12a²b-4ab²
c) (5a+b) (4a+b)= 20a²+5ab+4ab+b²=20a²+9ab+b²
d) (2x+5)²= (2x+5)×(2x+5)=4x²+10x+10x+25=4x²+20x+25
e) (5 y+ 4)²=(5 y+ 4)×(5 y+ 4)= 25y²+20y+20y+16=25y²+40y+16
f) ( 1/2 x - 2 )²= ( 1/2 x - 2 )×( 1/2 x - 2 )= ¼x²-x-x+4=¼x²-2x+4